The finance-dominated accumulation regime, income distribution and the present crisis - Stockhammer, Engelbert (Papeles de Europa, 2009)
The paper discusses the interactions of changes in income distribution and the accumulation dynamics in the post-Fordist accumulation regime in OECD countries, which is characterized by deregulated financial markets. The neoliberal mode of regulation came with a decisive shift in power relations at the expense of labor, which is clearly reflected in the fall of wage shares across OECD economies. The notion of a “finance-dominated” accumulation regime is proposed to highlight that financial developments crucially shape the pattern and the pace of accumulation. Financial globalization has relaxed balance of payment constraints and thereby allowed the build up of big international imbalances. The combination of real wage moderation and financial liberalization has led to different strategies (or at least outcomes) in different countries. While some countries (like the USA) exhibit a credit-fuelled consumption-driven growth model that comes with large current account deficits, others (like Germany and Japan) show an export-driven growth model with modest consumption growth and large current account surpluses. Overall the financedominated accumulation regime is characterized by a mediocre growth performance and by a high degree of fragility.